2016
DOI: 10.5505/tjtes.2016.47650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the open and laparoscopic appendectomy operations with respect to their effect on serum IL-6 levels

Abstract: BACKGROUND: Postoperative serum inflammatory cytokine levels are thought to reflect the magnitude of surgical stress. Cytokine interleukin-6 (IL-6) is an early marker of systemic inflammatory response and tissue damage. This study evaluated levels of IL-6 after open and laparoscopic appendectomy to compare the degree of surgical stress associated with these procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The authors found that there were no significant differences in the extent of the inflammatory response between the two surgical types for pancreatoduodenectomy. Contrastingly, in another study that looked at laparoscopic versus conventional open appendectomy, postoperative IL-6 levels were significantly lower in the former group, signifying that there may be a potential correlation between the magnitude of surgical stress and inflammatory markers [141]. In colonic cancer patients, laparoscopic surgery conferred lower serum IL-6 and VEGF levels compared to open colectomy; however, local levels of the inflammatory and angiogenic cytokines were not significantly different between the two groups [142].…”
Section: Discussionmentioning
confidence: 81%
“…The authors found that there were no significant differences in the extent of the inflammatory response between the two surgical types for pancreatoduodenectomy. Contrastingly, in another study that looked at laparoscopic versus conventional open appendectomy, postoperative IL-6 levels were significantly lower in the former group, signifying that there may be a potential correlation between the magnitude of surgical stress and inflammatory markers [141]. In colonic cancer patients, laparoscopic surgery conferred lower serum IL-6 and VEGF levels compared to open colectomy; however, local levels of the inflammatory and angiogenic cytokines were not significantly different between the two groups [142].…”
Section: Discussionmentioning
confidence: 81%
“…Several earlier studies have reported the superiority of LA over OA in terms of faster postoperative recovery [25,34], lower complication rates [21,35], and shorter LOS [36,37]. In addition, meta-analyses of several retrospective studies showed that IA was associated with fewer complications [38].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to include only patients who are allocated to undergo minimally invasive surgery was made based on the following rationale: every surgery is an insult to the human body and, therefore, generates an inflammatory response. It has been suggested by several studies that the minimally invasive approach initiates less of an inflammatory response as compared to the open approach [ 39 42 ]. Hence, we felt that including only patients who will have minimally invasive surgery creates a more homogeneous study population and a fairer comparison.…”
Section: Discussionmentioning
confidence: 99%